A Simple Method for Simulating Drought Effects on Plants - Marchin, Renée M.; Ossola, Alessandro; Leishman, Michelle R.; Ellsworth, David S. (Frontiers in Plant Science, 2020)
Drought is expected to increase in frequency and severity in many regions in the future, so it is important to improve our understanding of how drought affects plant functional traits and ecological interactions. Imposing experimental water deficits is key to gaining this understanding, but has been hindered by logistic difficulties in maintaining consistently low water availability for plants. Here, we describe a simple method for applying soil water deficits to potted plants in glasshouse experiments. We modified an existing method (the ‘Snow and Tingey system’) in order to apply a gradual, moderate water deficit to 50 plant species of different life forms (grasses, vines, shrubs, trees). The method requires less maintenance and manual handling compared to other water deficit methods, so it can be used for extended periods of time and is relatively inexpensive to implement. With only a few modifications, it is possible to easily establish and maintain soil water deficits of differing intensity and duration, as well as to incorporate interacting stress factors. We tested this method by measuring physiological responses to an applied water deficit in a subset of 11 tree/shrub species with a wide range of drought tolerances and water-use strategies. For this group of species, stomatal conductance was 2–17 times lower in droughted plants than controls, although only half of the species (5 out of 11) experienced midday leaf water potentials that exceeded their turgor loss (i.e. wilting) point. Leaf temperatures were up to 8 °C higher in droughted plants than controls, indicating that droughted plants are at greater risk of thermal damage, relative to unstressed plants. The largest leaf temperature differences (between droughted and well-watered plants) were in species with high rates of water loss. Rapid osmotic adjustment was observed in leaves of five species when drought stress was combined with an experimental heatwave. These results highlight the potential value of further ecological and physiological experiments utilizing this simple water deficit method to study plant responses to drought stress.